Identification of Subsurface Geological Structures from Gravity Data by Modelling Techniques in Kalak-Bardarash Area, West of Erbil City Iraqi Kurdistan Region - Ghaib, Fadhil A.; Mohammed A. Ahmad Salaee (Zanco Journal of Pure and Applied Sciences, 2024)
A quantitative interpretation of gravity anomalies in the Kalak-Bardarash area, west of Erbil City in the Kurdistan Region of Iraq, was performed using two-dimensional analysis techniques. These techniques modeled geological structures identified from a previously created Bouguer anomaly map of the area. Five profiles were selected for the analysis, resulting in eight models constructed for both deep and shallow-seated rock units. The deep-seated rocks are represented by the basement rocks, with models constructed in the NNE-SSW, WNW-ESE, and NW-SE directions using the regional anomaly component. The depth of the basement rocks ranges from five to nine kilometers and is affected by numerous faults in the form of graben and step structures. The basement rock surface slopes towards the NE and ESE at a gradient of 110 m/km. The shallow-seated rocks are represented by the sedimentary cover, which includes Neogene, Paleogene, and Cretaceous-aged groups of formations. The residual component of the anomalies of the five profiles were interpreted. Three profiles, oriented NNE-SSW and nearly perpendicular to the main anticlinal structure, revealed that the Bardarash anticline is influenced by two faults striking both limbs and extending in the NNW-SSE direction, with an estimated throw of 200 meters on each side. The southern fault is believed to extend down to the basement rocks. The other two profiles, oriented NW-SE and nearly perpendicular to the Zab River, indicated the presence of two additional faults with a throw of approximately 600 meters in the deeper parts striking the basement rocks, dipping towards the southeast. The throw of these faults gradually decreases upward in the sedimentary cover, reaching about 200 meters. These faults directly influence the course of the Zab River, directing it in a NE-SW direction at this district.